Strategi Mengelola Beban Kerja Menggunakan Infografis di DPRD Kota Palembang - Itryah; Firdaus, Najalina Velis (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2025)
The Palembang City Regional Representative Council (DPRD) acts as a liaison between the government and the people. Through recess activities, hearings, and public dialogues, council members listen directly to the needs and complaints of the community, then bring them to official forums for discussion. Public information disclosure is also an important aspect so that the community can monitor and assess the performance of the DPRD transparently. The method used during community service activities involves utilizing infographics to transform abstract information into more visually accessible forms through a dual-processing system implemented at the Secretariat of the Palembang City DPRD. The results of the community service activities revealed that the primary challenge stems from high workloads caused by suboptimal task distribution and communication. The use of infographics has proven effective in simplifying information, supporting task distribution, and helping staff work more focused and efficiently. From an industrial and organizational psychology perspective, infographics also play a role in reducing cognitive load and fostering a proactive work environment. Therefore, infographics are worthy of development as a practical strategy to enhance work effectiveness and well-being within the government sector.